The Chromatin Landscape of Cellular Senescence. Issue 11 (November 2016) - Criscione, Steven W.; Teo, Yee Voan; Neretti, Nicola
Abstract : Cellular senescence, an irreversible growth arrest triggered by a variety of stressors, plays important roles in normal physiology and tumor suppression, but accumulation of senescent cells with age contributes to the functional decline of tissues. Senescent cells undergo dramatic alterations to their chromatin landscape that affect genome accessibility and their transcriptional program. These include the loss of DNA–nuclear lamina interactions, the distension of centromeres, and changes in chromatin composition that can lead to the activation of retrotransposons. Here we discuss these findings, as well as recent advances in microscopy and genomics that have revealed the importance of the higher-order spatial organization of the genome in defining and maintaining the senescent state. Trends: Novel methods to investigate genome organization [high-throughput whole-genome conformation-capture (Hi-C)] have revealed that senescent chromosomes undergo a global spatial reorganization that can alter transcription and can explain some of the observed chromatin changes [e.g. senescence-associated heterochromatin foci (SAHFs)]. Loss of interaction between the lamina and constitutive heterochromatin induces large-scale changes in chromosome organization in cellular senescence. Centromere decondensation is an early event shared by many types of senescence and is potentially a new marker for the identification of senescent cells. SIRT6 is an early responder to DNA damage and is involved in satellite distension and derepression of retrotransposons. Change in the accessibility of heterochromatic regions leads to the mobilization of retrotransposons, which might contribute to the propagation of genomic instability.